Optimization for the production of mycelial biomass from Benjaminiella poitrasii to isolate highly deacetylated chitosan - Mane, S. R.; Pathan, Ejaj K.; Kale, D.; Ghormade, Vandana; Gadre, Ramchandra V.; Rajamohanan, Pattuparambil Ramanpillai; Badiger, Manohar V.; Deshpande, Mukund V. (Journal of Polymer Materials, 2017)
Benjaminiella poitrasii, a dimorphic zygomycetous fungus contains more chitosan in the mycelial cell wall than the cell wall of its yeast form. The optimized medium containing yeast extract, peptone, MgSO4, KH2PO4, trace metals (Fe2+, Mn2+ Zn2+ and Co2+ ) solution and 1% starch produced 10-12 g/L(dry wt.) of mycelial biomass in 48 h in a 2L fermenter. Using 1N NaOH treatment from 1 g of dried biomass 51.00 ± 0.52 mg of chitosan of 42.82 KDa molecular weight and 94.24 % degree of deacetylation was extracted. With Metarhizium anisopliae chitin deacetylase (CDA), chitosan yield was 59.00 ± 0.84 mg while treatment with CDA of B. poitrasii it was 78.05 ± 0.58 mg/g of dry wt. of biomass. The chitosan dissolved in 2% acetic acid showed higher antifungal activity against Candida albicans (MIC90 0.025 mg/mL) and Candida glabrata (MIC90 0.2 mg/mL) than chitosan extracted from marine source (MIC90 >1.6 mg/mL) suggesting use of fungal chitosan in healthcare.